2009
DOI: 10.1039/b904277f
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic structures and properties of lead chromium phosphate Pb3Cr2(PO4)4

Abstract: Single crystals of lead chromium phosphate Pb 3 Cr 2 (PO 4 ) 4 were grown by a flux technique and characterized by X-ray powder and single crystal diffraction, differential thermal analysis, polarized light microscopy and magnetic measurements. Two polymorphic structures have been identified: a monoclinic Pb 3 Cr 2 (PO 4 ) 4 of space group P2 1 /c ( 14) and a tetragonal Pb 3 Cr 2 (PO 4 ) 4 of space group P4 1 2 1 2 (94), and their phase correlation is described. Both structures consist of a three-dimensional f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…We found that the green colour is due to the presence of CrBO 3 . [33] Similarly, Mn III substitution also formed multiple phases consisting of LiMgBO 3 and Li 2 MnO 3 . The red colour of the product is attributed to the presence of Li 2 MnO 3 ; optical absorption spectra ( Figure S6) show features characteristic of Li 2 MnO 3 .…”
Section: Colour and Optical Characterisationmentioning
confidence: 98%
“…We found that the green colour is due to the presence of CrBO 3 . [33] Similarly, Mn III substitution also formed multiple phases consisting of LiMgBO 3 and Li 2 MnO 3 . The red colour of the product is attributed to the presence of Li 2 MnO 3 ; optical absorption spectra ( Figure S6) show features characteristic of Li 2 MnO 3 .…”
Section: Colour and Optical Characterisationmentioning
confidence: 98%
“…In recent years, inorganic metal phosphates have been part of intensive research activities both in high-temperature solid state and aqueous solution conditions, and their number has grown steadily [1][2][3]. Thec rystal chemistry of these compounds with anionic partial structures mainly built from PO 4 …”
Section: Discussionmentioning
confidence: 99%